The Effectiveness Of The Participatory Supervision Education Policy 'Empowered Women Supervise' Bawaslu North Sumatra - lubis, Suryanti; Beby Masitho Batubara; Walid Musthafa Sembiring (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
The effectiveness of participatory monitoring education policy is a key factor in increasing women's involvement in election monitoring. This study analyzes the implementation model of the Women Empowered to Supervise program organized by Bawaslu North Sumatra. Using an empirical approach, this study explores how training programs, socialization, and collaboration with community organizations are able to increase the capacity of women as active and empowered election supervisors. The results show that comprehensive training has strengthened women's understanding of how to effectively monitor elections. Socialization through digital media and community-based approaches has succeeded in increasing women's awareness and involvement in election monitoring. In addition, collaboration with women's organizations, academics and youth groups expanded the reach of the program and provided support for women in facing challenges in the field. This study confirms that structured and sustainable participatory oversight education contributes to improving the quality of democracy and electoral transparency. With more inclusive and participatory policies in place, women can play a more significant role in maintaining electoral integrity in Indonesia.Keywords: Election Supervision, Women, Political Participation, Democracy, Bawaslu North Sumatra